2018
DOI: 10.3892/ijmm.2018.3930
|View full text |Cite
|
Sign up to set email alerts
|

THR1 mediates GCN4 and CDC4 to link morphogenesis with nutrient sensing and the stress response in Candida�albicans

Abstract: Candida albicans (C. albicans) CDC4 (CaCDC4), encoding the F-box protein for the substrate specificity of the Skp1-cullin-F-box E3 ubiquitin ligase complex, suppresses the yeast-to-filament transition in C. albicans. In our previous study, Thr1 was identified as a CaCdc4-associated protein using affinity purification. THR1 encodes a homoserine kinase, which is involved in the threonine biosynthesis pathway. The present study generated a strain with repressible CaCDC4 expression and continuous THR1 expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…C. albicans cells lacking THR1 accumulate the toxic biosynthetic intermediate homoserine and are attenuated in terms of virulence and die rapidly upon threonine starvation and serum incubation ( Kingsbury and McCusker, 2010a , b ). Moreover, C. albicans THR1-depleted mutants exhibited increased sensitivity to oxidative and osmotic stress ( Lee et al, 2018 ). Regarding the phylogenetic analysis, different findings have been reported globally.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans cells lacking THR1 accumulate the toxic biosynthetic intermediate homoserine and are attenuated in terms of virulence and die rapidly upon threonine starvation and serum incubation ( Kingsbury and McCusker, 2010a , b ). Moreover, C. albicans THR1-depleted mutants exhibited increased sensitivity to oxidative and osmotic stress ( Lee et al, 2018 ). Regarding the phylogenetic analysis, different findings have been reported globally.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these ndings suggest that other signaling pathways are likely involved in the C. albicans oxidative stress response to H 2 O 2 . The transcription factor Stp2 is reported to contribute to nutrient adaption/sensing and bio lm formation in C. albicans via targeting the rapamycin (TOR) signaling pathway [40][41][42][43]. Therefore, investigating whether our ve identi ed transcription factors participate in the TOR signaling pathway in the presence of ROS is an intriguing area of future interest.…”
Section: Discussionmentioning
confidence: 99%
“…F-box protein plays crucial roles in plant growth and development as well as plant responses to environmental stimuli by tagging the substrate to proteasomal degradation [29]. In the Candida albicans CDC4 (CaCDC4) that encodes the F-box protein, it was found that the cells with loss of CaCDC4 were sensitive to oxidative stress and osmotic stress [30]. The F-box protein Fbx15 has been shown to regulate stress responses, gliotoxin production, environmental adaptation and virulence in Aspergillus fumigatus [31].…”
Section: Discussionmentioning
confidence: 99%